2018
DOI: 10.1177/0022487118755699
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Teaching Quality of Secondary Mathematics and Science Residents: A Classroom Observation Framework

Abstract: This study assesses the reliability of two observation rubrics, one in math and the other in science, and documents how the rubric data were used to inform a teacher education program. Classroom observations are typically considered essential for assessing teaching practice, yet many popular observation frameworks, while comprehensive in aim, do not appropriately capture key features of teaching valued by teacher education programs. Many of these tools do not attend to issues of equity, humanizing pedagogy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…For example, some view what they call the "dominant accountability paradigm" (Cochran-Smith et al, 2018) as reflecting market ideology and neoliberalism in education, privileging subject matter and often disconnected from the experiences and needs of students and teachers from nondominant communities (Lipman, 2011;Richmond, Bartell, & Dunn, 2016). Others call for building on what they see as a rich body of research that identifies knowledge and skills aimed at promoting democratic and socially just education and commitments in practice (e.g., Cochran-Smith et al, 2009;Crowley & Apple, 2009;Kumashiro, 2015;McDonald, 2005;Zeichner, Payne, & Brayko, 2014 This poses a dilemma for teacher education, which we have described in earlier editorials (Richmond et al, 2016): As we necessarily work within a system that warrants accountability, how might we "reclaim" accountability (Cochran-Smith et al, 2018) to support teacher candidates' preparation for the realities of today's schools and for their effective participation in "critical democracy" (Carter Andrews, Richmond, & Floden, 2018)? In this editorial, we call for casting a broader net that is both (a) more comprehensive with respect to the knowledge, skills, and practices evaluated and (b) more inclusive of the types of measures we use to obtain data.…”
mentioning
confidence: 99%
“…For example, some view what they call the "dominant accountability paradigm" (Cochran-Smith et al, 2018) as reflecting market ideology and neoliberalism in education, privileging subject matter and often disconnected from the experiences and needs of students and teachers from nondominant communities (Lipman, 2011;Richmond, Bartell, & Dunn, 2016). Others call for building on what they see as a rich body of research that identifies knowledge and skills aimed at promoting democratic and socially just education and commitments in practice (e.g., Cochran-Smith et al, 2009;Crowley & Apple, 2009;Kumashiro, 2015;McDonald, 2005;Zeichner, Payne, & Brayko, 2014 This poses a dilemma for teacher education, which we have described in earlier editorials (Richmond et al, 2016): As we necessarily work within a system that warrants accountability, how might we "reclaim" accountability (Cochran-Smith et al, 2018) to support teacher candidates' preparation for the realities of today's schools and for their effective participation in "critical democracy" (Carter Andrews, Richmond, & Floden, 2018)? In this editorial, we call for casting a broader net that is both (a) more comprehensive with respect to the knowledge, skills, and practices evaluated and (b) more inclusive of the types of measures we use to obtain data.…”
mentioning
confidence: 99%
“…Many authors point to issues that need to be considered when selecting and/or using a COS (e.g., Bell et al, 2012;Cohen & Goldhaber, 2016;Hill, Charalambous, Blazer, et al, 2012;Nava et al, 2018;Sandilos, 2012;van der Lans, van de Grift, van Veen, & Fokkens-Bruinsma, 2016). Generating valid and reliable scores by means of a COS is not self-evident.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A manual can also include guidelines concerning the recommended observation period (e.g., 30 minutes), when to score the observation form (e.g., at the end of the lesson), and how to act during the observation (e.g., stay at the periphery of the action), since this is likely to affect the scores provided by raters. Considering that multiple studies have shown that the reliability of the scores improves if the number of raters increases Nava et al, 2018), manuals can also include guidelines concerning the number of raters per teacher.…”
Section: Rating Quality Measuresmentioning
confidence: 99%
See 2 more Smart Citations